1988
DOI: 10.1128/cmr.1.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Overview of medically important antifungal azole derivatives

Abstract: Fungal infections are a major burden to the health and welfare of modern humans. They range from simply cosmetic, non-life-threatening skin infections to severe, systemic infections that may lead to significant debilitation or death. The selection of chemotherapeutic agents useful for the treatment of fungal infections is small. In this overview, a major chemical group with antifungal activity, the azole derivatives, is examined. Included are historical and state of the art information on the in vitro activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
185
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(195 citation statements)
references
References 260 publications
1
185
0
Order By: Relevance
“…The first group of azoles developed was the imidazoles between 1960s and 1980s, such as econazole, miconazole and ketoconazole ( Figure 2F-H) [38]. However, these drugs displayed a variety of limitations, including high toxicity, low efficacy and poor absorbance as well as severe side effects such as liver and gastrointestinal complications [6,39].…”
Section: Current Classes Of Antifungalsmentioning
confidence: 99%
“…The first group of azoles developed was the imidazoles between 1960s and 1980s, such as econazole, miconazole and ketoconazole ( Figure 2F-H) [38]. However, these drugs displayed a variety of limitations, including high toxicity, low efficacy and poor absorbance as well as severe side effects such as liver and gastrointestinal complications [6,39].…”
Section: Current Classes Of Antifungalsmentioning
confidence: 99%
“…Croconazole is a synthetic imidazole derivative (phenyl vinyl derivative), which has been shown to be a potent topical antifungal agent against dermatophytes (the causative organisms of tinea infections) and yeasts [Candida albicans] (Thesen, 1995). It has broad spectrum activity against variety of fungal species in vitro (Fromtling, 1988). It has been proved superior to clotrimazole but less active than miconazole and econazole against C. albicans (Ogata et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…These tests were carried out using five fungal species, some of them are pathogenic for human and animals, namely Aspergillus flavus, C. albicans, Chrysosporium tropicum (keratinophyte), Penicillium chrysogenum and Trichophyton rubrum (dermatophyte). All fungal strains were selected based on their pharmacological and clinical relevance as reported previously (Ogata et al, 1983;Fromtling, 1988). All fungal species were cultivated on sabouraud-dextrose agar (Oxoid, England).…”
Section: Microbiology Studymentioning
confidence: 99%
“…Consequently, there is a need for effective and less toxic drugs for the treatment of patients with these infections. One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37).…”
mentioning
confidence: 99%